Recommended practices for electron beam welding and allied processes (American Welding Society, 2013)
This document presents Recommended Practices for Electron Beam Welding and Allied Processes. It is intended tocover common applications of the process. Processes definitions, safe practices, general process requirements, and inspection criteria are provided.
At head of title: An American National Standard."
"Approved by the American National Standards Institute February 5, 2013."
"Supersedes AWS C7.1M/C7.1:2004."
"AWS C7.1M/C7.1:2013."
Keywords: Electron beam welding.; elektronické knihy; electronic books